ANALISIS PROFITABILITAS, LEVERAGE DAN EARNING PER SHARE TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Lela Dwi Rizki Rahmawati, Sri; Syukrina E Janrosl, Viola (LPPM Universitas Putera Batam, 2022)
This study aims to identify the effect of profitability, leverage and earning per share onstock returns on the Indonesia Stock Exchange. The population and samples were takenfrom companies engaged in the food and beverage sector listed on the Indonesia StockExchange, the sample selection was carried out using a purposive sampling technique,namely the selection of samples based on predetermined criteria. Then obtained a sampleof 12 companies. The method used in this research is multiple linear analysis methodusing classical assumption test and hypothesis testing. This hypothesis test is carried outeither partially or simultaneously with the help of SPSS V-25 software. The conclusion ofthis study is that partially the profitability and earnings per share variables have asignificant effect on stock returns, while the leverage variable has no effect on stockreturns. However, simultaneously the variable of profitability, leverage and earning pershare have a significant effect on stock returns.